2016
DOI: 10.7314/apjcp.2016.17.1.341
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori Associated Gastritis Increases Risk of Colorectal Polyps: a Hospital Based-Cross-Sectional Study in Nakhon Ratchasima Province, Northeastern Thailand

Abstract: Background: Colorectal polyps are common in Thailand, particularly in the northeastern region. The present study aimed to determine any correlation between Helicobacter pylori-associated gastritis and colorectal polyps in the Thai population. Materials and Methods: A total of 303 patients undergoing esophagogastroduodenoscopy with colonoscopy for investigation of chronic abdominal pain participated in this study from November 2014 to October 2015. A diagnosis of Helicobacter pylori associated gastritis was mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Additionally, approximately 32% of patients with H. pylori-associated gastritis develop gastric ulcers, while only 2% -3% progress to GC (21). With our studies host genetic factors, the Mdm2 SNP309 GG homozygous genotype may be a risk factor for GC in Thai patients (22).…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, approximately 32% of patients with H. pylori-associated gastritis develop gastric ulcers, while only 2% -3% progress to GC (21). With our studies host genetic factors, the Mdm2 SNP309 GG homozygous genotype may be a risk factor for GC in Thai patients (22).…”
Section: Discussionmentioning
confidence: 93%
“…[3,6,8,9,19, Nineteen of them are cross-sectional studies [3, 6, 8, 19, 21-24, 25-28, 30, 31, 35, 37-40], and the remaining eight are case-control studies [9, 29, 32-34, 36, 41, 42]. Serology was utilized as the detection method for H. pylori in 14 studies [8, 9, 21, 23, 25-27, 31-35, 38, 39], pathology in 4 [3,22,40,42], UBT in 4 [6,37], CLO in 6 [19,24,30,36], and combining UBT and CLO in 2 [28,29] A flow chart describing the process of study selection is shown in Figure 1. For the meta-analysis, data were extracted from twenty-seven studies with a total of 68,410 patients, and the pooled OR for colorectal adenoma related to H. pylori infection was 1.51 (95% CI 1.39-1.63), although there was significant heterogeneity (p < 0.001) ( Table 1 and Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…[3,6,8,9,19, Nineteen of them are cross-sectional studies [3, 6, 8, 19, 21-24, 25-28, 30, 31, 35, 37-40], and the remaining eight are case-control studies [9, 29, 32-34, 36, 41, 42]. Serology was utilized as the detection method for H. pylori in 14 studies [8, 9, 21, 23, 25-27, 31-35, 38, 39], pathology in 4 [3,22,40,42], UBT in 4 [6,37], CLO in 6 [19,24,30,36], and combining UBT and CLO in 2 [28,29]. A flow chart describing the process of study selection is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%